2022
DOI: 10.1371/journal.pntd.0010704
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of circulating Salmonella Typhi strains in an urban informal settlement in Kenya

Abstract: A high burden of Salmonella enterica subspecies enterica serovar Typhi (S. Typhi) bacteremia has been reported from urban informal settlements in sub-Saharan Africa, yet little is known about the introduction of these strains to the region. Understanding regional differences in the predominant strains of S. Typhi can provide insight into the genomic epidemiology. We genetically characterized 310 S. Typhi isolates from typhoid fever surveillance conducted over a 12-year period (2007–2019) in Kibera, an urban in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…Typhi cases with DCS is below 20% (Britto et al 2018), although there is substantial variation between countries (Park et al 2018;Mutai et al 2018;Kariuki et al 2021;Ochieng et al 2022;Acheampong et al 2019;Al-Emran et al 2016;Lunguya et al 2012;Smith et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typhi cases with DCS is below 20% (Britto et al 2018), although there is substantial variation between countries (Park et al 2018;Mutai et al 2018;Kariuki et al 2021;Ochieng et al 2022;Acheampong et al 2019;Al-Emran et al 2016;Lunguya et al 2012;Smith et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In Asia, decreased ciprofloxacin susceptibility (DCS, defined as a ciprofloxacin minimum inhibitory concentration [MIC] >0.06 and <1 µg/µl) S. Typhi accounted for more than 60% of typhoid cases in Asia in 2011-15, which has led to the adoption of azithromycin and third generation cephalosporins as the first line therapy for typhoid fever in this region (Britto et al 2018). In the African region, the proportion of S. Typhi cases with DCS is below 20% (Britto et al 2018), although there is substantial variation between countries (Park et al 2018; Mutai et al 2018; Kariuki et al 2021; Ochieng et al 2022; Acheampong et al 2019; Al-Emran et al 2016; Lunguya et al 2012; Smith et al 2010). In Zimbabwe, the proportion of S. Typhi referred to the national reference lab that were resistant to ciprofloxacin increased from 4% to 22% between 2012 and 2017 (Mashe et al 2019), while a large outbreak of typhoid fever in Harare showed ciprofloxacin resistance rates of 33% amongst hospitalised patients (N’cho et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Only primary quantitative studies were selected from the search output. The title of the study, year of study, study setting, study design, MDR-TB confirmed number of cases, MDR-TB/HIV co-infection proportion, and the outcome explored were characteristics retrieved from the studies (Table 1) [9–13,14 ▪▪ ,15–21,22 ▪▪ ,23,24 ▪▪ ,25–29,30 ▪ ,31 ▪ ,32–36,37 ▪▪ ,38–48,49 ▪▪ ,50 ▪ ].…”
Section: Search Methodsmentioning
confidence: 99%
“…Of these, 198 (82.5%) were sequenced at Wellcome Sanger, 25 (10.4%) at Technical University of Denmark, and 17 (7.1%) at KEMRI-CGHR laboratories in Nairobi using previously described methods. 28 30 Data quality was checked using the FastQC v0.11.15 tool. 31 Assemblies were generated using Shovill (v1.0.4), excluding contigs with coverage below 30x.…”
Section: Methodsmentioning
confidence: 99%